El Análisis Cualitativo Comparado (QCA): Una herramienta para entender fenómenos complejos en las ciencias sociales - Garcia, Maria Alejandra; Urbani, Ilaria (2025)
This Learning Note introduces Comparative Qualitative Analysis (QCA), a hybrid method combining qualitative depth with quantitative logic to explore complex causality in social phenomena. Originating from sociology and comparative politics, QCA is particularly suited for small and medium sample sizes. It uses set theory and Boolean algebra to identify necessary and sufficient conditions that explain a given outcome, recognizing the principle of equifinality and asymmetric causality. The Note outlines the steps of QCA and presents a case study on citizen participation in hydropower resettlement processes in the Global South. The method's relevance for governance, public policy, and multidimensional sustainability issues is emphasized, positioning QCA as a valuable tool for both theoretical insight and practical application.